Analyzing the Effectiveness of Indomaret Employee Performance Management in Kamal: An Employee Interview-Based Case Study - Andini Cristina Santoso; Nabilah Khairunnisa; Alisya Nurrahmania; Iriani Ismail (International Journal of Economics and Management Research, 2025)
This study aims to analyze the effectiveness of employee performance management at Indomaret Kamal outlets in Bangkalan city, through a qualitative case study. The research method uses semi-structured interviews with an employee to explore their experiences and perceptions related to various aspects of work, including stock management, work relationships, and job satisfaction. The results of the analysis indicate weaknesses in the stock management system, characterized by inconsistencies between online and physical stock data, and lack of adequate supervision from management. This causes some best-selling products to sometimes run out before the next stock replenishment schedule, causing losses in the form of lost potential sales and customer dissatisfaction. In addition to stock problems, employees are also dissatisfied with management supervision which is considered inadequate, which causes difficulties in carrying out tasks and reduces work motivation. In conclusion, this study highlights the need to improve the stock management system, increase more effective and supportive supervision, and employee training programs to improve the effectiveness of performance management at Indomaret. By implementing these recommendations, it is hoped that the effectiveness of employee performance management at Indomaret Kamal can be increased, which will ultimately have a positive impact on company productivity and customer satisfaction.